Incretin hormone responses to carbohydrate and protein/fat are preserved in adults with sulfonylurea‐treated KCNJ11 neonatal diabetes - Pamela Bowman; Kashyap A Patel; Timothy J McDonald; Jens J Holst; Bolette Hartmann; Maria Leveridge; Beverley M Shields; Suzie Hammersley; Steve R Spaull; Bridget A Knight; Sarah E Flanagan; Maggie H Shepherd; et al. (Journal of Diabetes Investigation, 2023)
Abstract The incretin hormones glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP), are thought to be the main drivers of insulin secretion in individuals with sulfonylurea (SU)‐treated KCNJ11 permanent neonatal diabetes. The aim of this study was to assess for the first time the incretin hormone response to carbohydrate and protein/fat in adults with sulfonylurea‐treated KCNJ11 permanent neonatal diabetes compared with that of controls without diabetes. Participants were given a breakfast high in carbohydrate and an isocaloric breakfast high in protein/fat on two different mornings. Incremental area under the curve and total area under the curve (0‐240 minutes) for total GLP‐1 and GIP were compared between groups, using non‐parametric statistical methods. Post‐meal GLP‐1 and GIP secretion were similar in cases and controls, suggesting this process is adenosine triphosphate‐sensitive potassium channel‐independent. Future research will investigate whether treatments targeting the incretin pathway are effective in individuals with KCNJ11 permanent neonatal diabetes who do not have good glycemic control on sulfonylurea alone.